The Treatment of Bronchopneumonia in Children With Urfamycin - Harry Hardjatno Ch.; A. H. Tagor; Ali Asfar; B. M. Akif; M. Sutan Assin (Paediatrica Indonesiana, 1974)
The aim of this study is to evaluatethe clinical responses of the thiam-phenicol in bronchopneumonia inchildren under 2 years of age, whowere hospitalized in the Departmentof Child Health, Dr. Tjiptomangunku-sumo General Hospital, in comparisonwith Penicillin-Chloramphenicol.